Penggunanan Media Kartu Pasangan: Apakah Meningkatkan Hasil Belajar Materi Waris dan Wasiat pada Siswa Madrasah Aliyah? - Muhammad Thohir; Torikhul Wasyik (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2021)
The low learning outcomes of students in understanding inheritance and will is considered a result that leads to the learning process of teachers in conservative classrooms using the lecture method. This study aims to determine the increase in student learning outcomes in inheritance and will material if given learning action using the pair card media. By using a classroom action research method, this study applies the use of pair card media through two cycles. Each cycle consists of four stages (planning, implementing, observing, reflecting). The results of the study before using cotton media (pair cards) the average score of students was 66.75 with 10 students' individual completeness, 36% classical completeness, and after using classroom action research in 2 cycles, cycle 1 produced an average score of 74 students. with 19 students' individual completeness, classical completeness increased to 68%. Then in the second cycle the average score was 85, individual completeness 27 students, and classical completeness became 96%. This empirical evidence shows that the pair card media is proven to improve student learning outcomes on inheritance and referee material. (Here you can add non-numeric findings as discussion/reflection in 1-2 sentences). The problems in Cycle I were many students who were not serious in participating in learning activities, because they did not understand the benefits of inheritance and will, and teachers had not prepared their partner card media properly. So that in Cycle II a reflection is held by providing insight into the importance of inheritance and will, as well as educators to better prepare the learning media facilities as early as possible before class action is carried out. After the improvement of student learning outcomes on inheritance and wills with partner cardmedia increased